2023
DOI: 10.1002/cre2.763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of denture cleansers on color stability and surface roughness of denture bases fabricated from three different techniques: Conventional heat‐polymerizing, CAD/CAM additive, and CAD/CAM subtractive manufacturing

Mehrab Takhtdar,
Nahid Azizimoghadam,
Mohammad Hasan Kalantari
et al.

Abstract: PurposeDenture base materials are commonly exposed to different denture cleansers which can affect their essential properties. This study aimed to assess the effect of denture cleansers on color stability and surface roughness of poly methyl methacrylate (PMMA) denture bases fabricated from different techniques: Conventional heat‐polymerizing, CAD/CAM additive and CAD/CAM subtractive.Materials and MethodsIn this in vitro study, 24 disc‐shaped specimens were fabricated by the mentioned methods for each group. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Coffee, red tea, and cola were assessed in the current study as they are the most consumed staining beverages in the daily diet (Al-Shami et al, 2023;Aydın et al, 2020), and distilled water was selected as Takhtdar et al, 2023) which considered an optimal period to obtain a cumulative effect. In addition, according to Aydin et al ( 2020), 30 days of exposure to certain beverages would reproduce 2.5 years of regular consumption, and a day of exposure would reproduce 30 days of consumption.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Coffee, red tea, and cola were assessed in the current study as they are the most consumed staining beverages in the daily diet (Al-Shami et al, 2023;Aydın et al, 2020), and distilled water was selected as Takhtdar et al, 2023) which considered an optimal period to obtain a cumulative effect. In addition, according to Aydin et al ( 2020), 30 days of exposure to certain beverages would reproduce 2.5 years of regular consumption, and a day of exposure would reproduce 30 days of consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were immersed in the medium for a day, 7 days, and 30 days. The maximum duration of immersion was 30 days, according to many studies (Al‐Shami et al, 2023 ; Takhtdar et al, 2023 ) which considered an optimal period to obtain a cumulative effect. In addition, according to Aydin et al ( 2020 ), 30 days of exposure to certain beverages would reproduce 2.5 years of regular consumption, and a day of exposure would reproduce 30 days of consumption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study evaluating the effect of denture cleaners on the color stability and surface roughness of PMMA denture bases fabricated with different techniques, it was observed that denture cleaners with alkaline pH, especially NaClO, affected the surface roughness and color stability of PMMA. Among the PMMA acrylic denture bases fabricated by three different methods, the highest surface roughness was found in the thermosetting PMMA material group [ 24 ].…”
Section: Discussionmentioning
confidence: 99%